PROSEDUR PEMERIKSAAN MAGNETIC RESONANCE IMAGING (MRI) BRAIN PERFUSI DENGAN METODE ARTERIAL SPIN LABELING (ASL) PADA PASIEN TUMOR - Novelin Safitri Maulida; Edy Susanto; Emi Murniati (JRI (Jurnal Radiografer Indonesia), 2019)
Background : Examination procedure of Magnetic resonance imaging (MRI) Brain Perfusion in patient with tumor disease at Radiology Department of National Brain Hospital used the MR Perfusion sequence with the Dynamic Susceptibility Contrast (DSC) method with the addition of Arterial Spin Labeling (ASL) method which was also used to determine CBF values. Nevertheless CBF values can also be obtained from the use of the DSC method. The application of these two roles in patient with tumor disease certainly has their respective roles in providing accurate information for the diagnosis. The purpose of this study was to determine the role of the application of MR perfusion with the Arterial Spin Labeling (ASL) method and the Dynamic Susceptibility Contrast (DSC) method for the diagnosis of patient with tumor disease at Radiology Department of National Brain Hospital. Methods :The type of this research is qualitative with case study approach. The data were collected from March – April 2019 at at Radiology Department of National Brain Hospital by using observation method, interview with radiology specialist doctor, sending doctor, FGD, and documentation. Data obtained from the study were analyzed by making the transcript then reduced in the form of categorization table and open coding, presented in quote form and then can be drawn conclusion. Result : Brain perfusion MRI examination procedures in tumor patients begin with examination preparation, preparation of tools and materials, carry out the examination using the MRI Brain protocol with contrast and without contrast. The use of contrast uses the Dynamic Susceptibility Contrast (DSC) method and non-contrast use using the Arterial Spin Labeling (ASL) method where both complement each other to inform perfusion parameter values. Conclusion : The conclution of this study indicate still needed the application of both MR perfusion methods, namely the ASL method and the DSC method. The ASL method will provide additional information in the form of absolute values of Cerebral Blood Flow that are not affected by permeability, besides that the DSC method is able to provide Cerebral Blood Volume values that are used as a parameter of Perfusion MR evaluation. Keyword : ASL, DSC, Tumor, CBF